2013
DOI: 10.1371/journal.pone.0074015
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of the p43 Mitochondrial T3 Receptor Increases Sertoli Cell Proliferation in Mice

Abstract: Among T3 receptors, TRα1 is ubiquitous and its deletion or a specific expression of a dominant-negative TRα1 isoform in Sertoli cell leads to an increase in testis weight and sperm production. The identification of a 43-kDa truncated form of the nuclear receptor TRα1 (p43) in the mitochondrial matrix led us to test the hypothesis that this mitochondrial transcription factor could regulate Sertoli cell proliferation. Here we report that p43 depletion in mice increases testis weight and sperm reserve. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Sertoli cells represent a paradigmatic model of transition between a proliferative state and commitment to differentiation that is controlled by FSH [81,82] and by other factors like thyroid hormones [83], which both act antagonistically. Seminal knock-out experiments in mice have demonstrated that thyroid hormones are the master signal that arrests Sertoli growth via the α isoform of the thyroid hormone receptor [84][85][86]. Local autocrine/paracrine secretion of other factors, such as glial cell-derived neurotrophic factor (GDNF) [63], activin A, and insulin-like growth factor (IGF)-I [87] also synergize, or at least complement, FSH action.…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Sertoli cells represent a paradigmatic model of transition between a proliferative state and commitment to differentiation that is controlled by FSH [81,82] and by other factors like thyroid hormones [83], which both act antagonistically. Seminal knock-out experiments in mice have demonstrated that thyroid hormones are the master signal that arrests Sertoli growth via the α isoform of the thyroid hormone receptor [84][85][86]. Local autocrine/paracrine secretion of other factors, such as glial cell-derived neurotrophic factor (GDNF) [63], activin A, and insulin-like growth factor (IGF)-I [87] also synergize, or at least complement, FSH action.…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 99%
“…This action on the positive regulators of the cell cycle is counteracted by T3, which downregulates the expression of cyclin-dependent kinase 4 [91], whose expression is upregulated by FSH in granulosa cells [92]. T3 likely inhibits molecular events occurring in early G1, and not later on, because neither the E, A and cyclins B nor cyclin-dependent kinase 2 (Cdk2) are modulated by T3 ( Figure 3) [84]. T3 acts not only through thyroid hormone receptor (TR)α1 but also through mitochondrial p43 receptors [84,85,91].…”
Section: Mechanism Of Action Of Fsh In the Sertoli Cellmentioning
confidence: 99%
“…Next, to investigate the functionality of mitochondria we performed electron microscopy studies of BAT from p43−/− animals, which did not suggest the occurrence of abnormal mitochondria (Fig. A) in contrast to our previous observations concerning the skeletal muscle and testis mitochondria. In addition, mtDNA content was only moderately reduced (−26%, P < 0.01) in 5‐month‐old p43−/− mice compared to WT animals (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…These studies will require generation of mice overexpressing p28 in selected lineages and/or at selected periods of development and the availability of specific knockout mice. The importance of elucidating p28 function in vivo is highlighted by our studies demonstrating the physiological importance of p43, clearly defined as a mitochondrial T3 receptor [9][10][11][12][13]41].…”
Section: Discussionmentioning
confidence: 99%